Analisis Efektivitas Peran BLK Komunitas dalam Upaya Meningkatkan Skill Tenaga Kerja Ditinjau dari Perspektif Ekonomi Islam - Siti Mutiah Ulfha; Andri Soemitra; Sugianto Sugianto (ITB AAS INDONESIA Surakarta, 2022)
The background of the problem in this study is that the original purpose of establishing the Community work exercise hall did not go as well as expected. Like, still increasing unemployment, the training process does not improve the workforce's skills to be better qualified. There is an absence of re-evaluation by the community work training hall to pre-training participants. This study determines the effectiveness of the role of community work exercise halls to improve the workforce's skills in Deli Serdang. This study uses the effectiveness theory introduced by Duncan, consisting of goal achievement, integration, and adaptation. The method used in this study is a qualitative descriptive method. The data analysis used in this study is an interactive analysis by miles and Huberman. Research results show that the effectiveness of the role of community work exercise halls has not been progressing effectively and optimally. This study concludes that the purpose of establishing the establishment of this Community Work Training Hall has not been fully achieved, the socialization implemented which is not yet optimal, and the lack of facilities needed to support the implementation of job training at the Community Work Training Hall. The researcher suggested that the community of work exercise halls conduct re-supervision, improve socialization, and consider setting up facilities for smooth job training implementation.